Pendekatan Lean Distribution Untuk Mengurangi Waste Pada Proses Distribusi Semen - Gholiyah, Salsabila; Saputra, Rizqi; Sholihah, Sita Aniisah; Chamsudi, Danie Hayam (Institut Transportasi dan Logistik Trisakti, 2024)
In a company that provides transportation and distribution services for bulk cement materials. The problem is the increasing delay that comes from waste in the cement distribution process. The purpose of this study is to find out the existing business processes and identify waste to make business processes more effective. The method used to conduct the research is Value stream Mapping, to facilitate the waste identification process, the Activity Mapping tool is used. Waste that has been identified is categorized according to seven waste. Based on the root cause of waste, a proposal for improvement is designed using the streamlining method. After being given a proposal to improve the recommendation, it can be described as a prediction of the future state map and the final result will be validated by simulation using Arena Software. Based on the results of the research, there are 2 categories of waste found in the process of shipping goods, the identified waste is waiting and transportation. After being given recommendations for proposed improvements, it is known that it can cut the process time by 9 hours and 10 minutes or 44% of the total cycle time.